PREFERENSI MAHASISWA DALAM BERWISATA: STUDI KASUS MAHASISWA SEKOLAH TINGGI PARIWISATA AMBARRUKMO (STIPRAM), YOGYAKARTA - Ahmad, Halim; Sigarete, Bayu Grendo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
Students are one of the important entities in the tourism market structure in Indonesia. Statistics show that the largest portion of tourist market in Indonesia based on employment status is students, where the university students are included in this category. Students potential market is represent the future of tourism market. This fact indicated how importance the knowledge about the student preferences in the tourism management, to create the better plan for capturing more tourists from this segment. Keywords: Tourism market, university students, preferences